About the design of morphing airfoils under uncertainties. Issue 1 (21st October 2015) - Fusi, Francesca; Quaranta, Giuseppe; Guardone, Alberto; Congedo, Pietro Marco
Abstract The paper presents an optimization framework for dealing with morphing airfoils for helicopter rotor blades. With regard to the morphing strategy, a conformable camber line is considered to deal with variable flow conditions encountered in forward flight with the objective of increasing the aerodynamic performance on the advancing and retreating sides of the rotor. Another peculiarity of the method is that the optimal shape is sought to be minimally sensitive to uncertainty in the operating conditions. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)